Policy Implementation Process and its Component on Tax Crime Investigation Boundary to Promote an Optimal Tax Revenue: A Literature Review - Chessa Ario Jani Purnomo; Gunadi Gunadi (Nagari Law Review, 2023)
Implementation of the policy to terminate a crime investigations in tax offenses through an administrative mechanisme is emphasizing the governance: responsibility for decision-making, accountability, supervision, and cooperation among domestic institutions. The research methodology employed in this article is a literature review. This article presents research data in the form of studies of policy implementation and authoritative documents such as laws and regulations, court decisions, and strategic plans of the tax authorities about tax criminal investigations. This article argues that several components must be considered in the policy implementation process associated with the mechanism for terminating tax criminal investigations, namely context, policy focus lens, innovation, levers of influence, facilitator or inhibitor, impact, policy actor, or leader of policy implementation. The results of this article's literature review indicate that the implementation of the policy of ending tax criminal investigations necessitates renewal of tax policy (PMK Number 55/PMK.03/2016) to support optimal tax revenue, including arrangements for working relations between the Ministry of Finance of the Republic of Indonesia and the Attorney General of the Republic of Indonesia, regulations delegating decision-making authority, and standard services at the request of tax authorities.